Sleep disorder among the adolescent using mobile phones in Nagarjun municipality, Nepal - Gurung, Jyoti; Godar, Suruchi; Thapa, Sujan; KC, Monica (Journal of Chitwan Medical College, 2026)
Introduction: Sleep disorder is a common health problem among adolescents, leading to poor academic performance. This study aimed to find out the prevalence of sleep disorders among adolescents using mobile phones in Nagarjun Municipality, Nepal. Methods: A descriptive cross-sectional study was conducted among adolescents aged 10-19 years from four private and one government school in Nagarjun Municipality, Nepal, from 24 Apr to 1 May 2023. Multi-stage cluster sampling was used. Data were collected using the Pittsburgh Sleep Quality Index (PSQI) and a self-structured questionnaire. Ethical approval was obtained. Data were analysed using SPSS version 23. Descriptive statistics were presented as n(%). A correlation test was used. A p<0.05 was considered significant. Results: Out of 400 students, mobile phone users were 358(89.5%) used mobile phones during bedtime, and 233(58.25%) used mobile phones during bedtime. Participants sleeping >7 hours were 371(93%). Based on PSQI score, all 400(100%) had sleep disorder: mild 383(95.8%) and moderate 17(4.3%). Headache was reported by 32(8%) and eye problem by 87(21.8%). No significant association was found between mobile phone use and sleep disorder (p=0.526) and between time spent on mobile after lights-off and sleep disorder (p=0.10). Socio-demographic factors showed no significant association. Conclusions: All adolescents had a sleep disorder, with the majority having mild disturbance. No significant association was found with mobile phone use. High prevalence indicates the need for sleep hygiene intervention.